1987
DOI: 10.1021/jm00391a012
|View full text |Cite
|
Sign up to set email alerts
|

Cardiotonic agents. 1. Novel 8-aryl substituted imidazo[1,2-a]- and -[1,5-a]pyridines and imidazo[1,5-a]pyridinones as potential positive inotropic agents

Abstract: Several 8-arylimidazo[1,2-a]pyridines, 8-arylimidazo[1,5-a]pyridines, and 8-arylimidazo[1,5-a]pyridinones were prepared and tested in vitro for potential cardiac inotropic and electrophysiological activity. Selected analogues were further tested in vivo in canine hemodynamic and cardiac electrophysiology models. Compounds having an imidazole substituent consistently showed activity. A pharmacophoric relationship between heterocycle-phenyl-imidazole and positive inotropic activity was noted. The significance of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
42
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(43 citation statements)
references
References 1 publication
0
42
0
Order By: Relevance
“…Among them the presence of benzimidazole [27] or benzothiazole [89] rings in numerous compounds is an important structural element for their biological and medical applications. For example benzimidazoles are widely spread in antiulcer, antihypertensive, antiviral, antifungal, anticancer, and antihistaminic medicines, among others [1012]. …”
Section: Introductionmentioning
confidence: 99%
“…Among them the presence of benzimidazole [27] or benzothiazole [89] rings in numerous compounds is an important structural element for their biological and medical applications. For example benzimidazoles are widely spread in antiulcer, antihypertensive, antiviral, antifungal, anticancer, and antihistaminic medicines, among others [1012]. …”
Section: Introductionmentioning
confidence: 99%
“…Literature survey revealed that imidazopyridines are pharmacologically important scaffolds that are known to exhibit a broad spectrum of biological activities like inhibitors of aromatase estrogen production suppressors [4], thromboxane synthetase [5], HCV replication [6], as well as melatonin receptor ligands [7], DNA directed alkylating [8], and cardiotonic agents [9]. This heterocyclic scaffold is also known to exhibit a variety of biological activities such as anticancer [10], anticoccodial [11], anticandidal [12], anticonvulsant [13], anti-inflammatory [14], antimicrobial [15], antioxidant [16], antitubercular [17], hypnoselective, anxioselective [18], and antiviral [19] activities.…”
Section: Introductionmentioning
confidence: 99%
“…One of the most widely used heterocyclic system from this group is imidazopyridine [1]. Imidazopyridines show a spectrum of biological activities like inhibitors of aromatase estrogen production suppressors [2], positive inotropic agents [3], platelet aggregation inhibitors, thromboxane synthetase inhibitors [4], antiviral [5,6], antibacterial [7], hypnoselective, and anxioselective activities [8]. Imidazopyridines exhibit different type of molecular mechanisms in cancer chemotherapy.…”
Section: Introductionmentioning
confidence: 99%